Toxic and Carcinogenic Effects of Dimethylnitrosamine (Dmna) in the Blue Fox (Alopex Lagopus) - Koppang, Nils (Acta Vet Scand, 2021)
Single doses of DMNA from 8 to 15 mg/kg body weight (B.W.) were given in the feed, by stomach tube or by subcutaneous application to 37 foxes. The course and intensity of the disease was not influenced by the application route, but was directly related to the amount of DMNA given per kg body weight, and caused hemorrhagic centrolobular liver necrosis and acute vessel changes especially in the hepatic vein system. The possibility of liver regeneration after a single DMNA exposure depends on the degree of damage in the hepatic vein system. Some animals can recover from the acute disease caused by DMNA. But if the hepatic vessel changes are enough pronounced, progressive changes occur in the hepatic vein system eading to liver cirrhosis. The observation period of the foxes after a single exposure was from 13 to 380 days. LD(50) should not be determined after a surviving time of 3 days but rather after 4 weeks. In our material LD(50) was 10 mg DMNA/kg B.W. In an experiment over a longer period of time 18 foxes divided into 3 groups were given 2 weekly doses of DMNA in food. They were treated with daily estimated doses of 1.0, 0.2 and 0.1 mg DMNA/kg B.W., respectively. The foxes in Groups 1 and 2 developed ascites, jaundice and liver failure after intake of 45–70 mg DMNA/kg B.W. The foxes in Group 1 treated with 1 mg DMNA/kg B.W. showed centrolobular hemorrhagic liver necrosis and productive vessel changes in the hepatic vein system. The second group given 0.2 mg DMNA/kg B.W. developed hemorrhagic centrolobular necrosis which healed with fibrosis leading to cirrhosis and chronic occlusion in many of the hepatic veins. In addition noduli of chondroid lamellae and foci of hematopoietic tissue and early stages of hemagiomatous liver tumors were found in the liver. The group exposed with 0.1 mg DMNA/kg B.W./day did not develop hemorrhagic centrolobular liver necrosis, but thickening in the walls of the hepatic veins. After more than 3½ years of exposure multiple hemangiosarcomae were growing out from the changed vessel walls. In an experiment over a shorter time period with daily exposure of DMNA doses in the feed below 0.15 mg/kg B.W., all the foxes were completely healthy and only some showed beginning changes in the hepatic vein walls. Hematomae were often seen in foxes dying after a single DMNA dose. One fox treated with 0.1 mg DMNA/kg B.W. died of brain bleeding after 220 days of treatment. Chronic vessel changes were found in the heart and kidneys of the DMNA treated foxes. These results emphasize the fact that DMNA gives vessel changes of a more general nature.